2005
DOI: 10.1007/s10930-005-6750-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Kinetic Properties of 6-Phosphogluconate Dehydrogenase from Rat Small Intestine

Abstract: 6-Phosphogluconate dehydrogenase (6PG) was purified from rat small intestine with 36% yield and a specific activity of 15 U/mg. On SDS/PAGE, one band with a mass of 52 kDa was found. On native PAGE three protein and two activity bands were observed. The pH optimum was 7.35. Using Arrhenius plots, Ea, DeltaH, Q10 and Tm for 6PGD were found to be 7.52 kcal/mol, 6.90 kcal/mol, 1.49 and 49.4 degrees C, respectively. The enzyme obeyed "Rapid Equilibrium Random Bi Bi" kinetic model with Km values of 595 +/- 213 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
5
15
1
Order By: Relevance
“…In the present study, the optimal than those reported in other studies, such as15 U/mg protein in rat small intestine [10] and 25 U/mg protein in rat kidney [17]; but higher than that in rat liver (0.207 U/mg and rat kidney cortex 0.056 U/mg [24]). Ceyhan et al [10] suggested that the specific activity of 6PGD showed great variability. For example, the specific activities of 6PGD from mammals were reported to range between 0.41 and 22.6 U/mg protein [5,8,9,13,25,26].…”
Section: Kinetic Behaviour Of 6pgdcontrasting
confidence: 60%
See 4 more Smart Citations
“…In the present study, the optimal than those reported in other studies, such as15 U/mg protein in rat small intestine [10] and 25 U/mg protein in rat kidney [17]; but higher than that in rat liver (0.207 U/mg and rat kidney cortex 0.056 U/mg [24]). Ceyhan et al [10] suggested that the specific activity of 6PGD showed great variability. For example, the specific activities of 6PGD from mammals were reported to range between 0.41 and 22.6 U/mg protein [5,8,9,13,25,26].…”
Section: Kinetic Behaviour Of 6pgdcontrasting
confidence: 60%
“…The molecular weight of the liver 6PGD from yellow catfish was 50.1 kDa by SDS-PAGE, similar to those in Dicentrarchus labrax L. liver [27], rat liver [13], rabbit mammary gland [25], human erythrocytes [26], sheep liver [28] and rat small intestine [10], lower than those in rat erythrocytes [5] and kidney [17], but higher than those in pig liver [8]. Generally speaking, dimer and/or tetramer is its active form for the enzyme, but dimer and tetramer possess different subunit mass.…”
Section: Kinetic Behaviour Of 6pgdsupporting
confidence: 54%
See 3 more Smart Citations